2022
DOI: 10.1051/0004-6361/202142768
|View full text |Cite
|
Sign up to set email alerts
|

The GAPS Programme at TNG

Abstract: The detection of lines in emission in planetary atmospheres provides direct evidence of temperature inversion. We confirm the trend of ultra-hot Jupiters orbiting A-type stars that show temperature inversions on their daysides by detecting metals emission lines in the dayside of KELT-20b. We first detected the planetary emission by using the G2 stellar mask of the HARPS-N pipeline, which is mainly composed of neutral iron lines, as a template. Using neutral iron templates, we performed a retrieval of the atmos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 51 publications
(49 reference statements)
4
26
0
Order By: Relevance
“…Our results show that HRS emission spectroscopy observations of hot gas giants have the potential to reveal much more information when treated as a phase curve rather than a single phase-collapsed emission spectrum, which is the approach that has most often been taken in the literature so far (e.g. Pino et al 2020;Yan et al 2020;Nugroho et al 2020;Borsa et al 2022). Conceptually, an HRS phase curve is similar to a classic lowresolution (LRS) phase curve observed from space (e.g.…”
Section: Hrs Phase Curves As a New Tool For Exoplanet Atmosphere Char...mentioning
confidence: 52%
See 2 more Smart Citations
“…Our results show that HRS emission spectroscopy observations of hot gas giants have the potential to reveal much more information when treated as a phase curve rather than a single phase-collapsed emission spectrum, which is the approach that has most often been taken in the literature so far (e.g. Pino et al 2020;Yan et al 2020;Nugroho et al 2020;Borsa et al 2022). Conceptually, an HRS phase curve is similar to a classic lowresolution (LRS) phase curve observed from space (e.g.…”
Section: Hrs Phase Curves As a New Tool For Exoplanet Atmosphere Char...mentioning
confidence: 52%
“…In other words, the westward offset in the peak scaling factor of iron lines found by Herman et al (2022), and confirmed with CO by van Sluijs et al ( 2022) can be interpreted as indirect evidence for an eastward hot-spot offset. Furthermore, based on HARPS-N emission spectroscopy, Borsa et al (2022) report evidence of asymmetry in thermal structure between pre-and post-eclipse spectra of UHJ KELT-20b, albeit not statistically significant. These authors also find that Fe ii and Cr i are only observable post-eclipse, and not pre-eclipse, despite achieving a similar total S/N across both phase ranges.…”
Section: Kelt-9b In the Context Of Ultra-hot Jupitersmentioning
confidence: 83%
See 1 more Smart Citation
“…We used the retrieval method developed by Yan et al (2020) to constrain the properties of WASP-33b's atmosphere. This method has already been successfully used to determine the thermal structure in the atmosphere of two other UHJs, WASP-189b and KELT-20b/MASCARA-2b (Yan et al 2020(Yan et al , 2022bBorsa et al 2022). In our implementation, we further developed this method for use with data from multiple instruments with different wavelength coverage.…”
Section: Retrieval Of the Atmospheric Propertiesmentioning
confidence: 99%
“…The atmospheric composition of UHJs has been extensively studied in recent years. For instance, neutral or ionic species of H, Li, O, Na, Mg, Si, K, Ca, Sc, Ti, V, Cr, Mn, Fe, Sr, and Y have been identified in the atmospheres of several UHJs, including KELT-9b (Yan & Henning 2018;Hoeijmakers et al 2018Hoeijmakers et al , 2019Wyttenbach et al 2020;Borsa et al 2021a), WASP-33b (Yan et al 2019(Yan et al , 2021Nugroho et al 2020a;Borsa et al 2021b;Cont et al 2021Cont et al , 2022Herman et al 2022), WASP-189b (Yan et al 2020;Stangret et al 2022;Prinoth et al 2022), WASP-76b (Seidel et al 2019;Ehrenreich et al 2020;Tabernero et al 2021;Deibert et al 2021;Casasayas-Barris et al 2021;Kesseli et al 2022), and KELT-20b/MASCARA-2b (Casasayas-Barris et al 2018, 2019Stangret et al 2020;Nugroho et al 2020b;Hoeijmakers et al 2020a;Rainer et al 2021;Yan et al 2022b;Borsa et al 2022). Also, the spectral signatures of an increasing number of molecular species such as CO, HCN, H 2 O, OH, SiO, or TiO have been identified in UHJ atmospheres (e.g., Nugroho et al 2021;Cont et al 2021;Landman et al 2021;Fu et al 2022;Prinoth et al 2022;Sánchez-López et al 2022;Yan et al 2022a;van Sluijs et al 2022;Lothri...…”
Section: Introductionmentioning
confidence: 99%